Evaluation of Risks and Benefits of Physical Activity of Hypertensives and Normotensives: Fighting a Societal Burden - Rui Brás; Dulce Esteves; Ricardo Gouveia Rodrigues; Paulo Duarte; Ana Gouveia; Kelly O'Hara; Paulo Pinheiro (Montenegrin Sports Academy, 2020)
Physical Activity (PA) is considered a coadjutant factor in the control of hypertension, helping to control this societal burden. This study investigates the factors that may influence the adoption of PA recommendations by hypertensive individuals by comparing physical activity patterns among hypertensives and normotensives and the importance placed on PA by both groups. Data from 966 Portuguese participants aged between 18 to 90 years old, representing hypertensives (n=144) and normotensives (n=822) were collected using a face-to-face questionnaire. The results show significant differences between the two groups in terms of causes of non-participation and dropping out, preferred PA activities, perceived knowledge, and information-seeking behaviour. The main barriers to exercise reported by hypertensives were the perception that PA is not adequate or even dangerous to their health. Doctors must be considered a key factor in promoting exercise. When compared to normotensives, hypertensives feel that PA information available is not appropriate (p=.0006). Hypertensives consider that existing programmes will not meet their needs and do not like traditional fitness classes, such as those in gyms. The fear of risks associated with exercise seems to be a significant barrier that impairs PA participation.